Usage of health information websites : a systematic review of older adults’ preferences for web features - Ng, Cheah Ping; Devinder Kaur Ajit Singh; Saravana Kumar; Tan, Maw Pin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Online health information have a role in enhancing health in older adults. However, age-related physiological changes and non-senior friendly websites proved to be a challenge for older adults. Research investigating older adults’ preferences of features in health information websites is limited. Thus, in this review, we aim to summarize older adults’ preferences regarding the design and content of health websites. Medline, CINAHL, Cochrane Library, Scopus, Journal of Medical Internet Research (JMIR) and Google Scholar were searched for relevant articles in February 2018, using key words ‘older adults’, ‘Internet’, ‘health information’ and ‘usability’. The methodological quality of included studies was evaluated using the McMaster critical appraisal tools by two independent reviewers. Individual study design, participants’ characteristics, and identified preferences for health website features were extracted and summarized narratively. (PROSPERO registration number: CRD42018096281). Five studies (3 qualitative, 2 quantitative) were included in this review. The quality appraisal score ranged from 32% to 83%. The web feature preferences of older adults were grouped into three domains: web presentation factors, web navigation factors and health information preferences. The results highlight older adults have specific preferences when engaging with online content. This review suggests that readable text, simple design, consistent layout and straightforward web navigation are the preferred priorities for a health information website for older adults. Findings from this review may be useful to healthcare professionals and developers to understand older adults’ preferences pertaining to web design and contents in health websites specifically designed for this population.